The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/9531074
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Localization of WT1 and Decrease of miRNA-16-1 in Nephrotic Syndrome

Abstract: Nephrotic syndrome (NS) is a glomerular disease that is defined by the leakage of protein into the urine and is associated with hypoalbuminemia, hyperlipidemia, and edema. Steroid-resistant NS (SRNS) patients do not respond to treatment with corticosteroids and show decreased Wilms tumor 1 (WT1) expression in podocytes. Downregulation of WT1 has been shown to be affected by certain microRNAs (miRNAs). Twenty-one patients with idiopathic NS (68.75% were SSNS and 31.25% SRNS) and 10 healthy controls were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Specifically, urine miR-200c levels in MCNS and FSGS patients were higher than patients with other diagnosis, while urine miR-192 levels were lower in DN patients compared to patients with other diagnosis. Zapata-Benavides et al reported that serum miR-16-1 levels in NS patients analyzed by qPCR were lower than healthy controls [ 24 ]. Teng et al also investigated the miRNA profile using serum samples with qPCR verification and reported that serum miR-181a, miR-210, miR-30a, miR-942, miR-192 and miR-586 levels were upregulated in NS patients [ 25 ].…”
Section: Mirnas In Nephrotic Syndromementioning
confidence: 99%
“…Specifically, urine miR-200c levels in MCNS and FSGS patients were higher than patients with other diagnosis, while urine miR-192 levels were lower in DN patients compared to patients with other diagnosis. Zapata-Benavides et al reported that serum miR-16-1 levels in NS patients analyzed by qPCR were lower than healthy controls [ 24 ]. Teng et al also investigated the miRNA profile using serum samples with qPCR verification and reported that serum miR-181a, miR-210, miR-30a, miR-942, miR-192 and miR-586 levels were upregulated in NS patients [ 25 ].…”
Section: Mirnas In Nephrotic Syndromementioning
confidence: 99%
“…Immunofluorescence staining was performed using 4-μm-thick frozen sections of renal biopsy specimens fixed in cold acetone for 3 min and air dried, as described previously [41]. Double immunofluorescence staining were carried out with rabbit polyclonal anti-LC3 (clone PM036; MBL) diluted 1:50 and mouse monoclonal anti-Wilms tumor 1 (WT1) (clone IR055; DAKO), the latter reacted with the cytoplasm of glomerular podocytes [42,43]. The sections were blocked in 3% bovine serum albumin for 1 hour at room temperature and then left overnight at 4˚C, and stained with the antibodies described above.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…Autophagic vacuoles were mainly detected in the cytoplasm of glomerular podocytes, seldom detected in that of glomerular mesangial cells or endothelial cells in renal biopsy specimens observed by EM (Fig 1). The localization of LC3, a marker of autophagy, was investigated by co-staining with antibodies to WT1, which are expressed in the cytoplasm of glomerular podocytes in nephrotic syndrome [43]. Most of the LC3-positive podocytes in the glomerulus were co-positive for WT1 (Fig 2), suggesting that autophagy mainly occurred in the glomerular podocytes.…”
Section: Morphological Evidence Of Autophagy In Renal Biopsy Specimensmentioning
confidence: 99%
“…2a). been shown to decrease after the onset of glomerular disease 17,18 . However, in BALB/cJ isolated glomeruli, we observed a several-fold increase in Wt1 expression after ADR treatment, before Wt1 fell to low levels ( Supplementary Fig.…”
Section: Transient Increase Of Podocyte Gene Expression In Adr-injurementioning
confidence: 99%